Multiple independent introductions of HIV-1 CRF01_AE identified in China: what are the implications for prevention? - Yassir F Abubakar (Public Library of Science (PLoS), 2013)
Background HIV-1 CRF01_AE accounts for an important fraction of HIV infections in Asia including China, but little is known about the phylogenetic and evolutionary history of this CRF (circulating recombinant form). In the current study, we collected a large number of 1,957 CRF01_AE gag p17 sequences with known sampling year (1990-2010) from 5 global regions representing 15 countries to better understand the phylogenetic relationships and epidemic history of CRF01_AE strains in China. Methodology/principal findings CRF01_AE gag p17 sequences were retrieved from public databases to explore phylogenetic relationships and phylogeographic dynamics of CRF01_AE in Asia by using maximum-likelihood phylogenetics and Bayesian coalescent-based analyses. We found close phylogenetic relationships between sequences from Thailand, Vietnam and China. Moreover, at least 5 independent introductions and 5 independent autochthonous clades of CRF01_AE, which descended from Thailand or Vietnam were identified in China from 1991 through 2003. Conclusion/significance The current study not only defines the migration of CRF01_AE clades to/in Asia, but also demonstrates the criticalness of identifying the circulating strains in the population for the development of vaccine and microbicides.